Technology readiness and satisfaction in Vietnam's luxury hotels. (2019) - Huy, Le Van; Nguyen, Pham Thi Hoan; Pham, Long; Berry, Ronald
The objective of this study was to examine the relationships among customer's technology readiness, technology acceptance, and satisfaction with technologies commonly available in luxury hotels. The data for this study was collected from 828 international tourists who stayed in luxury hotels in Vietnam. The results showed that optimism and innovativeness positively influenced perceived ease of use, while four dimensions of technology readiness positively influenced perceived usefulness. In addition, optimism, discomfort, and insecurity had impacts on customer satisfaction with technologies. Moreover, perceived ease of use had impacts on perceived usefulness and on customer satisfaction with technologies. Finally, theoretical contributions, managerial implications, and future research directions are discussed.